On Becoming and Being an Entrepreneur: Exploratory Study on Hamka’s Works, Lembaga Budi - Rahmad Hakim (Universitas Darussalam Gontor, 2024)
Entrepreneurship is a type of work that is very interesting and challenging with lots of competition. However, in order to become a successful entrepreneur, some capital and skills are required. This study aims to find out the skills that entrepreneurs need to have in starting a business in Hamka’s work entitled Lembaga Budi. Primary and secondary data were collected from Hamka’s works and other works that have a focus relevant to this research. The data collected was analyzed using content data analysis, namely by combining topics relevant to entrepreneurship. The results of this study reveal, according to Hamka, that to become a successful entrepreneur, at least several important things are needed, namely: knowledge related to entrepreneurship, self-confidence, great will, work and time planning, focus on the company or job, the role of government in the entrepreneurial sector, the importance maintaining trust, maintaining product or service quality, conducting market research, promotion strategies and excellent service to customers. The results of this study contribute to enriching discourse in entrepreneurship, especially in Islamic entrepreneurship and the role of ethics in business.